Risk factors of Helicobacter pylori infection in an urban community in Northeast Brazil and the relationship between the infection and gastric diseases - Basílio,Irigrácin Lima Diniz (2018)
Abstract INTRODUCTION: Helicobacter pylori, a water contaminant, is the primary pathogenic agent associated with gastric diseases in humans. Exposure to H. pylori is more likely higher in developing countries. This study aimed to evaluate the risk factors associated with H. pylori infection in patients undergoing endoscopy to validate the cause of dyspeptic symptoms in an urban population in northeast Brazil and to compare the urease test and polymerase chain reaction assay results with the histopathological findings. METHODS: We evaluated 200 of 759 individuals with dyspeptic complaints from Campina Grande, State of Paraiba, northeast Brazil. Patients underwent endoscopy, followed by gastric biopsies. Logistic regression analysis was performed to adjust for confounders and to determine significant risk factors of dyspeptic disorders. RESULTS: Women accounted for 72.5% (145/200) of the participants. Approximately 59.8% (120/200) of the samples tested positive for H. pylori based on histological examinations. The specificity of polymerase chain reaction assay was higher than that of the urease test (77% vs. 64%, p=0.034). City drinking water [odds ratio (OR): 2.6; 95% confidence interval (CI): 1.3-5.21; p=0.004] and smoking (OR: 4.0; 95% CI: 1.13-14.5; p=0.031) were the risk factors of H. pylori infection. Belching was the most common symptom associated with H. pylori infection (p=0.05). CONCLUSIONS: The increased risk of H. pylori infection associated with non-treated water consumption indicates the need for improvements in public water treatment and better sanitary conditions because these can be a source of not only H. pylori infections but also other water-borne pathogen infections.